Interleukin 22 and its association with neurodegenerative disease activity - Chen, Wenjian; Wang, Jianpeng; Yang, Huaizhi; Sun, Yuankai; Chen, Bangjie; Liu, Yuchen; Han, Yanxun; Shan, Ming; Zhan, Junfeng (Frontiers in Pharmacology, 2022)
It's worth noting that neuroinflammation is well recognized as a symptom of neurodegenerative diseases (NDs). The regulation of neuroinflammation becomes an attractive focus for innovative NDs treatment technologies. There is evidence that IL-22 is associated with the development and progression of a wide assortment of NDs. For example, IL-22 can activate glial cells, causing them to generate pro-inflammatory cytokines and encourage lymphocyte infiltration in the brain. IL-22 mRNA is highly expressed in Alzheimer's disease (AD) patients, and high expression of IL-22 has also been detected in the brains of patients with other NDs. We examine the role of IL-22 in the development and treatment of NDs in this review, and we believe that IL-22 has therapeutic potential in these diseases..